PENGARUH MODEL PEMBELAJARAN ROLE PLAYING TERHADAP KEMAMPUAN LITERASI SISWA KELAS V PADA MATA PELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR (JS (JURNAL SEKOLAH), 2025)
Abstract: The purpose of this study was to determine how much influence the Role Playing learning model has on the literacy skills of fifth grade students in Indonesian language lessons. The first problem found was that students were not very interested in reading because they were more interested in short videos. In this study, a quasi-experimental method was used. There were two classes, an experimental class and a control class. The experimental class used the Role Playing model for learning, while the control class used the regular lecture method. The results of the experimental class before treatment were 56.25, but after treatment it increased to 79.17. Meanwhile, the control class only increased by 65.00 from 50.38. The experimental class had an average increase score (N-Gain) of 56.87%, higher than the control score of 31.19%. The results of the t-test showed a significance value of p of 0.001 and an effect size (Cohen's d) of -1.199, indicating that the effect was large. In short, the role playing model succeeded in improving students' literacy skills in all aspects, including reading, writing, speaking, and listening. This model can be used as an alternative for learning Indonesian in elementary schools because it makes the learning atmosphere more active and enjoyable. Keyword: role playing, literacy, Indonesian language, elementary students, quasi-experiment Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui seberapa besar pengaruh model pembelajaran Role Playing terhadap kemampuan literasi siswa kelas V dalam pelajaran Bahasa Indonesia. Masalah pertama yang ditemukan adalah siswa tidak terlalu tertarik untuk membaca karena mereka lebih tertarik pada video pendek. Dalam penelitian ini, metode quasi eksperiment digunakan. Ada dua kelas, kelas eksperimen dan kelas kontrol. Kelas eksperimen menggunakan model Role Playing untuk pembelajaran, sedangkan kelas kontrol menggunakan metode ceramah biasa. Hasil kelas eksperimen sebelum perlakuan adalah 56,25, tetapi setelah perlakuan menjadi 79,17 meningkat . Sementara itu, kelas kontrol hanya naik 65,00 dari 50,38. Kelas eksperimen memiliki skor peningkatan (N-Gain) rata-rata sebesar 56,87%, lebih tinggi dari skor kontrol 31,19%. Hasil uji t-test menunjukkan nilai signifikansi p sebesar 0,001 dan ukuran efek (Cohen's d) sebesar -1,199, yang menunjukkan bahwa efeknya besar. Singkatnya, model role playing berhasil meningkatkan kemampuan literasi siswa dalam semua aspek, termasuk membaca, menulis, berbicara, dan menyimak. Model ini dapat digunakan sebagai alternatif untuk pembelajaran Bahasa Indonesia di sekolah dasar karena membuat suasana belajar lebih aktif dan menyenangkan.Kata Kunci: role playing, literasi, Bahasa Indonesia, siswa sekolah dasar